The complex construction of a glaciovolcanic ridge with insights from the 2021 Fagradalsfjall Eruption (Iceland) - Pollock, Meagen; Edwards, Benjamin R.; Judge, Shelley; Wallace, Chloe; Hiatt, Alex; Perpalaj, Aleksander; Was, Ellie; Hauksdóttir, Steinunn (Frontiers in Earth Science, 2023)
Glaciovolcanic landforms provide global-scale records of paleoenvironmental conditions and yield critical insights into subglacial eruption processes. Eruptions under ice are inherently dynamic with complex feedbacks between the magmatic system and cryosphere. Generic models for the formation glaciovolcanic ridges, or tindars, are relatively simple, but others have suggested more complicated lithostratigraphic and geochemical relationships. In order to test and build a more robust model, we conducted a comprehensive field-based and geochemical study of Undirhlíthar ridge on the Reykjanes Peninsula in southwest Iceland. Here, we show that the ridge was built through a complex sequence of eruptive and intrusive events under dynamically changing ice conditions. Field mapping documents that most of the ridge was built by multiple pulses of pillow lava emplacement, but periods of fragmentation from depressurization and/or edifice collapse were common. Rotating pillow plunges document the emplacement of discrete pillow-dominated lobes and the migration of volcanic activity between eruptive vents. Intrusions are up to 20 percent by area of exposed stratigraphy sequences. Variations in major elements, trace elements, and Pb-isotopes demonstrate that the eruption was fed from separate crustal melt reservoirs supplied by melts from a compositionally variable mantle source. A shift in mantle source signature correlates with decreasing water contents, suggesting the primary ridge-building phase was triggered by the injection of magma into the crust under thinning ice conditions that promoted transport of magma into the eruption zone. Variable water contents in quenched pillow rims record rapid changes in emplacement pressures over short distances. Our new work shows that the model for tindar construction should consider the significant role of intrusions in the growth of the ridge. The adjacent 2021-22 Fagradalsfjall eruptions allow us to draw parallels between fissure-fed eruptions in subaerial and ice-confined environments and test hypotheses about the volcanic systems on the Reykjanes Peninsula. Both eruptions may have been triggered by mixing events, erupted lavas with varying mantle source signatures, and focused volcanic activity along migrating vents. Differences in composition between the two locations capture momentary and complex interactions among the crustal magma plumbing system, mantle source heterogeneity, and the scales and mechanisms of melt extraction.